Epidemiological and laboratory profile of type 2 diabetic patients in a reference center in Aracaju/SE (Research, Society and Development, 2023)
Diabetes Mellitus (DM) is one of the most common chronic non-communicable diseases (NCDs) in the world and is the fourth leading cause of death across the globe. In addition to the human factor itself, its complications generate economic impacts on the health network, andonthe labor field, with significant losses in potential years by the economically active population. In view of this, the study carried out is paramoun the importance of not only trace a laboratory and clinical epidemiological profile of type 2 Diabetes Mellitus, but also its complications and risk factors. This, in turn, was a descriptive, longitudinal, retrospective and sectional study, which used quantitative data and collected from patient records, chosen at random, attended the Diabetes and Endocrinology Center Luciano Barreto Júnior in Aracaju - Sergipe, between August andDecember 2019. Socioeconomic Variables Were Assessed as well as comorbidities and complications of DM2. The sample of 200 patients characterized by a predominance of females (75.4%). The average age is 65.4 years, with the majority aged between 60-70 years (43.1%). Smoking in 3.1% only and alcoholism in 1.5%. 89.2% of the individuals evaluated are also dyslipidemic. Hepatic Steatosis Is Associated With Only 18.5% of patients, whereas SAH is 80%. Most patients (76.9%) fit the group with fasting blood glucose